Reading and Writing with Shirley Jackson's the Lottery. Issue 3 (2nd July 2020) - Philp, Hannah
ABSTRACT: I examine the ways in which reading in the classroom is a social practice and how that social practice can produce nuanced student texts that reflect a rich understanding of what has been read. In doing so, I also consider how the reading environment allows us to manipulate and embody texts in ways that allow for a more detailed understanding than the individual and solitary reading practices that seem to be prized in our society.